Myths of Venice : The Figuration of a State - Rosand, David (Book collections on Project MUSE., 2001)
"In this work, David Rosand explores the imagery Venice developed to represent the legends of its origins and legitimacy, its divine favor and holy purpose. These themes found public expression throughout the city: in the basilica of San Marco and the Ducal Palace, at the Rialto and in the decoration of the confraternities, and in the monuments of the Piazza, the Loggetta, and the Libreria di San Marco. Indeed, among the most significant political resources of the Most Serene Republic were the imagination and talents of her greatest artists - Gentile and Giovanni Bellini, Carpaccio, Titian, Jacopo Sansovino, Tintoretto, and Veronese - who gave enduring visual form to the myths of Venice." "Myths of Venice is concerned not only with the official iconography of state per se, but with the ways in which such imagery resonates within a culture, the ways in which visual motifs acquire an aura of association and allusion dependent upon a network of shared values and habits of interpretation."--Jacket